2012
DOI: 10.1039/c2nr31153d
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-free, water dispersible and highly luminescent dye nanoparticles for targeted cell imaging

Abstract: We develop a new strategy of using surface functionalized small molecule organic dye nanoparticles (NPs) for targeted cell imaging. Organic dye (2-tert-butyl-9,10-di(naphthalen-2-yl)anthracene, TBADN) was fabricated into NPs and this was followed by surface modification with an amphipathic surfactant poly(maleic anhydride-alt-1-octadecene)-polyethylene glycol (C18PMH-PEG) through hydrophobic interactions to achieve good water dispersibility and bio-environmental stability. It should be noted that no additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…[24][25][26] Indeed, owing to high brightness, biodegradability and capacity to encapsulate different cargos, dye-loaded polymer NPs emerged as a powerful alternative to inorganic nanoparticles, such as quantum dots, 27,28 dye-doped silica NPs, 29,30 etc. They have already found a variety of applications, including cellular and in vivo imaging, 31,32 , imaging of cellular uptake, [33][34][35][36] long-term cell tracking, 24,35 cell barcoding, 24 receptor-specific cell targeting, 31,37,38 single-molecule detection 39 and single-particle tracking 40 , biosensing, 41 as well as in vivo studies for visualizing tumors 42,43 , theranostics 44 , photodynamic therapy, 45 etc. On the other hand, dye-loaded polymeric NPs can model the behavior of drug-loaded NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Indeed, owing to high brightness, biodegradability and capacity to encapsulate different cargos, dye-loaded polymer NPs emerged as a powerful alternative to inorganic nanoparticles, such as quantum dots, 27,28 dye-doped silica NPs, 29,30 etc. They have already found a variety of applications, including cellular and in vivo imaging, 31,32 , imaging of cellular uptake, [33][34][35][36] long-term cell tracking, 24,35 cell barcoding, 24 receptor-specific cell targeting, 31,37,38 single-molecule detection 39 and single-particle tracking 40 , biosensing, 41 as well as in vivo studies for visualizing tumors 42,43 , theranostics 44 , photodynamic therapy, 45 etc. On the other hand, dye-loaded polymeric NPs can model the behavior of drug-loaded NPs.…”
Section: Introductionmentioning
confidence: 99%
“…This PEGylation resulted in a moderate size increase for GNPs, with the average hydrodynamic diameter of approximately 146 nm for PEGylated GNPs (pGNPs) ( Figure S3b, Supporting Information), which is compatible for EPR effect. [ 32,33 ] The resulting pGNPs were dark blue in color and showed excellent stability in physiological solutions ( Figure S3b-d, Supporting Information). PEGylation can signifi cantly increase the stability of GNPs and help them escape the clearance of reticuloendothelial system (RES)-associated organs with long circulation time.…”
Section: Preparation and Characterization Of Pgnpsmentioning
confidence: 95%
“…Another approach to specific targeting with π-conjugated molecules is through functionalization by folic acid (FA), which can bind to the folate receptor (FR), an overexpressed receptor in various types of cancer cells. It was demonstrated that 2-tert-butyl-9,10-di(naphthalen-2-yl)anthracene (TBADN) NPs encapsulated by FA-PEG could efficiently target and be internalized in FR-positive KB cells [107]. This platform was further improved with color tuning ability by co-incorporation of FRET acceptor dyes [108].…”
Section: Target-specific Imagingmentioning
confidence: 97%